The Effect of Sales Growth, Leverage, and Firm Size on Tax Avoidance (Empirical Evidence from the Food and Beverage Manufacturing Sector Listed on the Indonesia Stock Exchange during 2019–2023) - Ayu Mulan Amertasari; Desi Kurniawati (Sean Institute, 2025)
Tax avoidance remains a crucial issue within Indonesia’s tax system, particularly among corporate taxpayers striving to reduce their tax burden while complying with regulations. This study investigates the influence of sales growth, leverage, and firm size on tax avoidance in manufacturing companies operating in the food and beverage sector listed on the Indonesia Stock Exchange. Using a quantitative approach, the research employs secondary data sourced from audited financial statements and applies panel data regression analysis with the fixed effect model selected based on statistical testing. The findings reveal that sales growth has a significant negative effect on tax avoidance, indicating that companies with higher revenue growth are less inclined to engage in aggressive tax planning. On the other hand, leverage and firm size do not show a significant impact on tax avoidance. These results offer important insights for policymakers and stakeholders in developing more effective tax compliance strategies and corporate governance mechanisms.